2022
DOI: 10.1002/clc.23850
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of RDW alone and in combination with NT‐proBNP in patients with heart failure

Abstract: Background Red blood cell distribution width (RDW) and N‐terminal pro brain natriuretic peptide (NT‐proBNP) may predict the prognosis of heart failure (HF). However, the impact of combined RDW and NT‐proBNP levels as a prognostic marker of HF remains unclear and the significance of this combination at various time‐points has not been sufficiently studied. Hypothesis RDW can predict prognosis in HF at various time‐points and combination with NT‐proBNP improves the progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 39 publications
(65 reference statements)
1
32
0
Order By: Relevance
“…It is linked to iron, folate or vitamin B12 deficiency, red cell early destruction, and an inflammatory status which leads to bone marrow dysfunction, hepatic congestion and hematological disorders ( 20 , 21 ). As regards chronic HF, RDW has been reported to be a strong tool for HF prognosis ( 21 24 ) alone or in combination with NT-proBNP ( 25 ). Of note RDW is usually part of the data provided when a complete red blood cell count is requested and therefore is frequently available without a specific request and further economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is linked to iron, folate or vitamin B12 deficiency, red cell early destruction, and an inflammatory status which leads to bone marrow dysfunction, hepatic congestion and hematological disorders ( 20 , 21 ). As regards chronic HF, RDW has been reported to be a strong tool for HF prognosis ( 21 24 ) alone or in combination with NT-proBNP ( 25 ). Of note RDW is usually part of the data provided when a complete red blood cell count is requested and therefore is frequently available without a specific request and further economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional biomarker for the diagnosis and prognostic evaluation of HF, the clinical application of NT-proBNP is quite limited due to multiple factors[ 39 ], such as an advanced age and renal dysfunction[ 40 ]. Its effectiveness is further compromised in cases of HF with preserved ejection fraction (HFpEF), due to the impact from the clinical characteristics of HFpEF, including obesity, atrial fibrillation, and renal impairment[ 41 ]. Moreover, NT-proBNP levels may appear normal in the HFpEF patients, thereby impacting the accuracy of risk assessment[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oxidative stress shortens the lifespan of red blood cells and changes the distribution of red blood cell volume. RDW may reflect the inflammatory response, which is a powerful biomarker for long-term prognosis in patients with AHF ( 17 , 43 ). In a cohort study including 3231 patients with HF with a median follow-up of 2.9 years, those with RDW in the upper quartile had an increased risk of all-cause mortality, 120% and 114% increased risk of all-cause mortality (HR=2.20 [1.68–2.89]) and cardiovascular mortality (HR=2.14 [1.53–2.98]) respectively, compared to patients with RDW in the lower quartile ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…RDW may reflect the inflammatory response, which is a powerful biomarker for long-term prognosis in patients with AHF ( 17 , 43 ). In a cohort study including 3231 patients with HF with a median follow-up of 2.9 years, those with RDW in the upper quartile had an increased risk of all-cause mortality, 120% and 114% increased risk of all-cause mortality (HR=2.20 [1.68–2.89]) and cardiovascular mortality (HR=2.14 [1.53–2.98]) respectively, compared to patients with RDW in the lower quartile ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation